Evaluating Outcome in Mechanically Ventilated Young Patients at a Pediatric Intensive Care Unit - Muhammad Jamil, Iqbal Ahmed, Zahid Anwar, Waseem Pasha, Ibrahim, Usamah Saeed Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate outcome in mechanically ventilated young patients at a pediatric intensive care unit. Material and methods: This Study was conducted in the Department of Paediatrics, Shaihida Islam Teaching Hospital Lodhran in the duration from October, 2022 to March, 2023. We randomly sampled 154 pediatric ICU patients requiring mechanical breathing aged 1–10 years of both genders. The outcome of mechanically ventilated young patients at a pediatric intensive care unit was evaluated. Independent samples T test and Chi Square test were applied for assessing association keeping statistical significance at 0.05. Results: The mean age of the patients was 4.44±2.61 years, length of hospital stay 7.08±4.27 days. In our study 102 (66.2%) patients survived while 52 (33.8%) had expired. Outcome had significant association with type of cases and length of hospital stay. Conclusion: From our study we conclude that the expiry rate of the children admitted for mechanical ventilation was 33.8%. Keywords: Mechanical ventilation, Pediatrics, Pediatric Intensive Care Unit, Critical illness.